Android based smart security systems using internet of things (IoT) and firebase - Harvent Rau, Mogana Ravu (2019)
This application is named as “Android based Smart Security System using IoT and Firebase” where it is an anti-burglar concept implementation by using an innovation device with less cost and easy to get. It acts by notifying the users as the device sends push up notifications to the user if any motion detected at the target location. This will aware the user how important is smart security for their life, property and family member. There are several problem statements related to customer requirements. Users are lack of awareness of thief protection as it is one of most frequent crimes nowadays thus this device will assist user to have security for themselves. Users will face many losses of his/her valuable properties due to not implementing any security device inside the home, workplace or other place. Finally, most of the users are very busy people with different working background and they do not have any time to monitor their selfbelonging due to its busy working hours. The objectives for this system are to design an innovation monitoring system using ESP8266 Nodemcu and Ultrasonic sensor. Moreover, this system is also designing a push up notification system using an API communication, python language and Node.js language. The methodology that has been chosen is waterfall model. As a result, this system is successfully detect the human movement, send a signal to the firebase using Wi-Fi module (Nodemcu), from firebase send a push up notification via API communication to user android and lastly develop an innovation monitoring device. After user gets the notification, user can take the necessary actions.